Panton-valentine leukocidin, mecA, and SCCmecV in methicillin-resistant Staphylococcus aureus isolates sampled from hospitalized patients in Northern Iran - Amirmozafari, Nour (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Panton-Valentine Leukocidin (pvl) is associated with strains of Staphylococcus aureus that produce a high level of virulence. The aim of this study was to investigate the prevalence of pvl gene and its relationship with mecA and SCCmecV in isolated samples taken from hospitalized patients in northern Iran. Materials and Methods: During a 6-month treatment period, a total of 92 clinical isolates of S. aureus were obtained. Resistance to methicillin was determined, and the prevalence of pvl gene was estimated through running a polymerase chain reaction (PCR) on chromosomal DNA. The pvl positive isolates were further analyzed for mecA and SCCmecV genes by PCR. Results: In total, 18 isolates (19.56%) were shown to be positive in terms of their carrying the pvl gene, and from among them, 15 isolates were methicillin-resistant S. aureus (MRSA), 3 were methicillin-susceptible S. aureus, and 8 were positive for mecA gene. None of the pvl positive samples had the SCCmecV gene cassette. Conclusions: The study found that the majority of pvl positive isolates were MRSA, and almost half of them had the mecA gene. Based on the results, it could be postulated that there is a significant relationship between these two variables; however, they were not correlated in regard to SCCmecV.